2008
DOI: 10.1196/annals.1447.001
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of Helicobactor pylori May Trigger Onset of Type 1 Diabetes

Abstract: In patients with idiopathic thrombocytopenic purpura (ITP), which is considered an autoimmune disease, eradication of Helicobacter pylori cures a significant number of patients. However, here we report an adult patient who developed type 1 diabetes (T1D), which is also considered an autoimmune disease, after eradication of Helicobacter pylori. Although further investigation is needed to understand the pathophysiology of T1D, we would like to emphasize that clinicians should consider the risk of its development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…3 However, another case report from Japan indicated that the eradication of H. pylori might trigger the onset of type 1 diabetes. 4 Although our study is limited by the fact that it is a retrospective analysis from one center with a small number of subjects, the present findings suggest that eradication therapy for H. pylori does not, at least profoundly, affect glycemic control in Japanese subjects with type 2 diabetes. Further investigation is needed to determine whether autoantibodies against insulin or islet cells possibly triggered by H. pylori infection might be an irreversible process.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…3 However, another case report from Japan indicated that the eradication of H. pylori might trigger the onset of type 1 diabetes. 4 Although our study is limited by the fact that it is a retrospective analysis from one center with a small number of subjects, the present findings suggest that eradication therapy for H. pylori does not, at least profoundly, affect glycemic control in Japanese subjects with type 2 diabetes. Further investigation is needed to determine whether autoantibodies against insulin or islet cells possibly triggered by H. pylori infection might be an irreversible process.…”
Section: Discussionmentioning
confidence: 52%
“…3 However, another case report from Japan indicated that the eradication of H. pylori might trigger the onset of type 1 diabetes. 4…”
Section: Discussionmentioning
confidence: 99%
“…Dore et al found that Hp frequency was lower in a small group of 12–19-year-old adolescents with T1DM compared to age-matched controls (9.0 vs. 25.0%); however, statistical significance was absent [22]. In 2008, Tada et al [23] speculated that eradicating Hp triggered T1DM in an adult by a case report. On the other hand, some authors reported that the Hp infection frequency in T1DM did not differ from the infection rate observed in the control groups by 13 C urea breath test (UBT) or serology [12‒15].…”
Section: Discussionmentioning
confidence: 99%
“…Helicobacter pylori (Hp) bacteria are the most prevalent cause of infection and inflammation in the foregut. Formerly, the presence of Hp infection in CD or T1DM subjects was found indifferent compared to controls [8][9][10][11][12][13][14][15]; however, contradictory data exist [16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…On a similar trend, another group showed that H. pylori infected patients had a significantly higher HOMA‐IR level (diagnostic standard of insulin resistance) when compared with uninfected ones [90]. In a Japanese case report, the authors reported the onset of type 1 diabetes mellitus after H. pylori eradication [91]. The link with an autoimmune mechanism remains unclear.…”
Section: Other Diseasesmentioning
confidence: 90%